Usage of Forceps and Dormia basket in the Management of Ureteric Stone: Comparison between Holmium: YAG Laser and Pneumatic Lithotripsy in a Referral Hospital, Bangladesh (Bangladesh Medical Journal, 2019)
Now lithoclast has become more popular tool than various intracorporeal lithotripters for the treatment of ureteric stones. Recently the Holmium:YAG laser has been used with a wide range of potential urological applications, including intracorporeal lithotripsy of ureteric stones. This study was conducted to compare the use of Forceps and Dormia basket in the management of ureteric stone between Holmium: YAG Laser and Pneumatic Lithotripsy. It was a longitudinal follow-up comparative study conducted at Combined Military Hospital, Dhaka. All the respondents were admitted patients in Combined Military Hospital Dhaka, under Urology Ward. A total of 100 patients were enrolled for this study under convenient purposive sampling method. They all were admitted with the complaints of upper ureteric stone who underwent ureteroscopic lithotripsy from October 2010 to September 2012. In 50 patients, Laser Lithotripsy (LL) was used and in other 50 patients Pneumatic Lithotripsy (PL) was used. Same ureteroscope, video monitor, baskets and irrigation devices were used in both the samples. Patients were followed up after 1st and 3rd months interval. Lithotripsy follow-up was done with radiograph and ultrasonography of kidney, ureter and bladder.  Patients with migrated fragments or incomplete clearance were underwent an auxiliary procedure such as shock wave lithotripsy. Mean stone size was 1.36 ± 0.36 cm in group Laser lithotripsy (LL) and 1.37± 0.36 cm in group Pneumatic lithotripsy (PL). The immediate stone clearance rate was significantly higher in Group LL (94.0%) than Group PL (76.0%). Proximal migration of fragments were 6.0% in LL group and 24.0% in PL group. Use of stone retrieval equipment (baskets, forceps) was 16.0% and 64.0% in LL and PL group respectively (p